Study the alteration of cardiac rhythm in hypertensive patients by 24-hour electrocardigraphy holter - Nguyễn, Tấn Quân; Hoàng, Anh Tiến; Hồ, Anh Bình (Vietnam Journal of Diabetes and Endocrinology, 2023)
Hypertension is one of major causes leading to cardiac arrhythmias, including dangerous arrhythmias that threaten patients survivals [3]. Besides detecting types, frequencies, durations of cardiac arrhythmias…, 24 hour- ECG holter helps to know mechanism leading to arrhythmia affected by automatic nervous system. Alteration of cardiac rhythm by analysis of time and frequency on 24 hour- ECG holter helps in prognosis of cardiac patients Objectives: Patients diagnosed with hypertension according to Vietnam Heart Association 2008 [2]. Method: Cross- sectional study. Resuts: - The ratio of hypertensive classification is equivalent between grade 1,2,3 : 35,42%; 32,33%; 32,25%. - In our study, HRV index in hypertensive: SDNN: 81,51; ASDNN: 41,32; SDANN : 72,90; RMSSD: 30,03 compared with index of alteration of cardiac rhythm in normal people: 122,89; 55,69; 110,26; 37,5 (p< 0,001). - Grade 3 hypertension group has the highest rate in retinopathy (p > 0,05). - Group patients with kidney damage have lower ASDNN than in group without kidney damage (p = 0,027). Conclusions: 24-hours ECG holter helps to detect, follow-up cardiac arrhythmia, alteration of cardiac rhythm in hypertensive patients